Characterization of endothelin-converting enzyme 1 as a key enzyme in the multienzyme Aβ degradation pathway - Irem Ulku; Fatima El Ansari; Mark A. Hancock; Hedi Zhou; Gael Cagnone; Jean-Sebastien Joyal; Teddy A. J. Fisher; Timothy E. Kennedy; Filip Liebsch; Gerhard Multhaup (Proceedings of the National Academy of Sciences, 2025)
Altered β-amyloid (Aβ) homeostasis is a critical event triggering the shift from healthy aging to Alzheimer disease (AD) through the overproduction and impaired clearance of Aβ peptides. The Aβ-degrading enzymes (ADEs) are a collective group of proteases that normally promote clearance to counteract Aβ-induced neurodegeneration. We previously discovered that the beta-site amyloid precursor protein cleaving enzyme 1 is an atypical ADE that produces the nontoxic fragment Aβ34 by recognizing 40- or 42-residue-long Aβ peptides as substrates in vitro and in vivo. Here, we examined other known ADEs for their potential roles in degrading Aβ34, Aβ40, and Aβ42. By genetic, cellular, and pharmacological approaches, we identified and characterized endothelin-converting enzyme 1 (ECE1) in a human neuroblastoma cell line, human brain vascular pericytes, and primary rat cortical cultures as a major enzyme degrading Aβ34 but not Aβ40 or Aβ42. Notably, we found that ECE1 cleaves Aβ34, an indicator of amyloid clearance, to a unique and unusually stable Aβ20-34 fragment that has the potential to serve as a measurable biomarker. Biocomputational analyses from non-AD controls and individuals with AD pathology showed that the highest messenger ribonucleic acid (mRNA) levels of ECE1 expression were found in pericytes (i.e., cells within the brain microvasculature that are known to produce Aβ34) compared to other cell types. Given Aβ34 is an indicator for prodromal AD, we postulate that our collective findings (i.e., generation of Aβ34 and Aβ20-34 intermediates within the “amyloidolytic” degradation pathway) will generate a set of biomarkers to detect amyloid clearance activity in vivo.